Clean and Safe Drinking Water Systems via Metagenomics Data and Artificial Intelligence: State-of-the-Art and Future Perspective - Mahajna, Asala; Dinkla, Inez J. T.; Euverink, Gert Jan W.; Keesman, Karel J.; Jayawardhana, Bayu (Frontiers in Microbiology, 2022)
The use of next-generation sequencing technologies in drinking water distribution systems (DWDS) has shed insight to the microbial communities’ composition, and interaction in the drinking water microbiome. For the past two decades, various studies have been conducted in which metagenomics data have been collected over extended periods and analyzed spatially and temporally to understand the dynamics of microbial communities in DWDS. In this literature review, we outline the findings which were reported in literature on what kind of occupancy-abundance patterns are exhibited in the drinking water microbiome, how drinking water microbiome dynamically evolves spatially and temporally in the distribution networks, how different microbial communities co-exist and what kind of clusters exist in the drinking water ecosystem. While data analysis in the current literature concerns mainly with confirmatory and exploratory questions pertaining to the use of metagenomics data for the analysis of DWDS microbiome, we present also future perspective and potential role of artificial intelligence (AI) and mechanistic models to address the predictive and mechanistic questions. The integration of meta-omics, AI and mechanistic models transcends metagenomics into functional metagenomics, enabling deterministic understanding and control of DWDS for clean and safe drinking water systems of the future.